A comparative study between the results of learning Arabic for students who learn online with students who learn face to face in the Higher School of Muhammadiyah Pekanbaru / Dirâsah Muqâranah baina Natâ’iji Ta’allum al-Lughah al-Arabiyah li at-Thullâb allazina Yata’allamûna abro Internet ma at-Thulâb allazina Yata’allamûna Wajhan li Wajhin fi al-Madrasah al ‘Aliyah al-Muhammadiyah Pekanbaru - Wahyudi, Ahmad; Zulkifli, Zulkifli; Hidayat, Hakmi; Hakim, Sri Wahyuni; Zulbaida, Zulbaida (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
AbstractThe impetus for this research was a phenomenon that the researcher found about the differences in the results of Arabic language learning for students of the Muhammadiyah High School in Pekanbaru after applying online learning during the Covid-19 pandemic. The aim of this research is to find out the comparison between the results of learning Arabic for students who learn online with those who learn face to face. This research is quantitative with an experimental type of research. The population of this research are all students of the Muhammadiyah High School in Pekanbaru. Random sampling method was taken, which was taken from the tenth class of natural sciences and the tenth class of social sciences, where the tenth class of natural sciences was classified as an experimental class and the tenth class of social sciences as a control class. After conducting the pre- and post-test in the experimental and control classes, the results of this research showed that the results of the Kolmogorov-Smirnov normality test in the experimental class showed that sig. > α0.05, that is, 0.069 > 0.05 so that the data were normally distributed, and the control class showed that sig. > α0.05, is 0.879 > 0.05 so that the data were also normally distributed. The statistical test for thitung< ttabel shows 1,204 < 1,734, then H0 is accepted and Ha is rejected. Therefore, it can be concluded that there is no significant difference between the results of learning Arabic for students who learn online with students who learn face to face at Muhammadiyah Higher School of Pekanbaru.Keywords: Comparative Study, Results Of Learning Arabic, Online Learning, Face-To-Face Learning.ملخصكان الدافع وراء هذا البحث ظاهرة وجدها الباحث حول الاختلافات في نتائج تعلم اللغة العربية لطلاب المدرسة العالية المحمدية ببكنبارو بعد تطبيق التعلم عبر الإنترنت خلال جائحة Covid-19. يهدف هذا البحث هو لمعرفة المقارنة بين نتائج تعلم اللغة العربية للطلاب الذينيتعلمون عبر الإنترنت مع الطلاب الذين يتعلمون وجهًا لوجه. هذا البحث كمي مع نوع البحث التجريبي. مجتمع هذا البحث جميعهم من طلاب المدرسة العالية المحمدية ببكنبارو. تم أخذ أسلوب أخذ العينات عشوائياً (Random Sampling) والذي تم أخذه من الفصل العاشر للعلوم الطبيعية والفصل العاشر للعلوم الإجتماعية حيث تم تصنيف الفصل العاشر للعلوم الطبيعية كفصل تجريبي والفصل العاشر للعلوم الإجتماعية كفصل ضابط. بعد إجراء الاختبار القبلي والبعدي في الفصلين التجريبي والضابط ، أظهرت نتائج هذا البحث أن نتائج اختبار الحالة الطبيعية Kolmogorov-Smirnov في الفصل التجريبي أظهر أن sig.> α0.05 ، أي 0.069> 0.05 لذلك أن البيانات تم توزيعها بشكل طبيعي ، وأظهر الفصل الضابط أن sig.> α0.05 ، أي 0.879> 0.05 بحيث تم أيضًا توزيع البيانات بشكل طبيعي. يُظهر الاختبار الإحصائي لاختبار thitung < ttabel وهو 1.204> 1.734 ، ثم يتم قبول H0 ويتم رفض Ha. لذلك يمكن استنتاج أنه لا يوجد فرق كبير بين نتائج تعلم اللغة العربية للطلاب الذينيتعلمون عبر الإنترنت مع الطلاب الذين يتعلمون وجهًا لوجه في المدرسة العالية المحمدية باكنبارو.كلمات أساسية : دراسة مقارنة ، نتائج تعلم اللغة العربية ، التعلم عبر الإنترنت ، التعلم وجها لوجه.